Visceral larva migrans presenting as multiple liver abscesses. (October 2013) - Ramachandran, Jeyamani; Chandramohan, Anuradha; Gangadharan, Sajith Kattiparambil; Unnikrishnan, LS; Priyambada, Leena; Simon, Anna
Eosinophilic necrotizing granulomas in the liver, known as visceral larva migrans (VLM), are a rare cause of liver abscesses. The term VLM refers to infections in human tissues caused by the larval stages of ascarid worms of dogs and cats. We report two cases of VLM which presented with high grade fever and abdominal pain for 3-4 months. Marked peripheral eosinophilia, multiple confluent perivenous lesions in the right lobe of liver with characteristic migratory tracts on imaging and biopsy evidence of necrotizing eosinophilic granulomas led to the diagnosis. Complete recovery was achieved with repeated courses of a combination of anthelmintics.